Fermentation of water kefir beverage containing Ziziphus jujuba Mill. syrup : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Albany, New Zealand - Mu, Xinyi (Massey University, 2019)
Water kefir is a self-carbonated, low sugar beverage with a mildly sour taste fermented by a microbial multispecies of kefir dominated by lactic acid bacteria (LAB) and yeasts. The fermented beverage is popular due to its pleasant sensory characteristics and perceived health benefits. The presence of probiotics and antioxidants in the water kefir confer health benefits to consumers when consumed in sufficient amounts. The major antioxidant in jujube fruit is rutin which is related to the reducing of high-density lipoprotein cholesterol and fasting blood sugar in patients with diabetes mellitus. The fermented beverage (water kefir) is produced mainly at household and by small-scale artisans whereby sucrose is normally added as a source of carbon for the fermentation. Due to consumer demand for foods containing low calories and carbohydrates, there is an incentive to produce products with reduced amount of added sugar including fermented water kefir. Jujube contains a high amount of sugars. This study investigated the potential of using syrup extracted from Ziziphus jujuba Mill. (jujube) to partially replace added sucrose used for water kefir fermentation. Several water-bath methods were investigated for the extraction of the jujube syrup. The most efficient method consisted of 650 mL extraction water and the mixture (jujube and water) was extracted at 70°C. The syrup obtained by this method was subjected to further studies. Two concentrations of the jujube syrup (10%, 20%, v/v) and two fermentation temperatures (25°C, 27°C) were used for the jujube water kefir fermentation. Various analyses and measurements were conducted on the beverage during fermentation and storage (4°C). The beverages were analysed for sugar, acidity, antioxidants, titratable acid, while pH, colour, and total soluble solids were measured. Microbiological analyses of the beverages were also conducted. The beverages were subjected to sensory evaluation by an informal focus group and by consumer sensory panellists using a 9-point hedonic rating scale. The beverage with higher syrup concentration (%, v/v) contained higher total soluble solids and was darker than the sample containing a lower concentration of syrup (p<0.05). By the end of the fermentation period (72 h), the beverage with higher syrup concentration had higher cell counts of LAB and yeast. No differences (p>0.05) were observed between the total soluble solids of the beverages fermented at 25°C and 27°C. The fermented (27°C) jujube water kefir beverage (2.5% organic raw sugar, w/v; 20% jujube syrup, v/v for stage 1 fermentation) with added jujube syrup (20% v/v) in stage 2 was selected as the most promising formulation by consumer sensory panellists. At the end of the fermentation (72 h), the selected beverage contained ethanol (3.37±0.13% v/v), sucrose (0.17±0.03% w/v), glucose (0.92±0.14% w/v), fructose (1.44±0.08% w/v), lactic acid (0.14±0.00% w/v), acetic acid (0.37±0.02% w/v), and rutin (6.26±0.16% w/v). The high concentration of ethanol may be attributed to the conversion of lactic acid into ethanol by the LAB. After storage for 21 days (4°C), yeast counts had decreased (p<0.05) while LAB counts had decreased by about one log. The concentrations of the sugars and acetic acid had decreased whereas the concentrations of ethanol, rutin and lactic acid increased. Meanwhile, the overall acceptability sensory scores of the beverage had decreased after storage for 21 days (4°C). The results of this study indicated the potential of producing a low sugar jujube water kefir using reduced added sugar and jujube syrup. However, more research is required to reduce the ethanol content of the beverage to meet the requirement for low alcohol product in New Zealand. Also, further research is required to improve the stability of the beverage during refrigerated storage.
The following Figures were removed for copyright reasons but may be accessed via the sources provided: Figures 2.3 (=Stadie et al., 2013 Fig 5); 2.4 (=Fiorda et al., 2017 Fig 3); 2.5 (=Reddy et al., 2008 Fig 1); 2.6 (=van Dijken et al., 1993 Fig 2); 2.7 (=Waldherr et al., 2010 Fig 2B); 2.8 (=Fiorda et al., 2017 Fig 4); & 2.9 (=Fiorda et al., 2017 Fig 5).
Keywords: Fermented beverages; Jujube (Plant)